Development of the set models and a method to form information spaces of scientific activity subjects for the steady development of higher education establishments - Biloshchytskyi, Andrii; Kuchansky, Alexander; Andrashko, Yurii; Omirbayev, Serik; Mukhatayev, Aidos; Faizullin, Adil; Toxanov, Sapar (Eastern-European Journal of Enterprise Technologies, 2021)
This paper describes the basic conceptual apparatus required to form information spaces for scientific activity subjects. Multiple models have been built to identify collective and individual scientific activity subjects, including information on the subjects' publication citations, their abstracts, as well as their indicators in scientometric databases, etc. A conceptual scheme of interaction between collective and individual scientific activity subjects has been described, taking into consideration the dynamics of their productivity. A method has been proposed to form the information spaces for the collective and individual scientific activity subjects such as higher education establishments and scientists. The method involves a series of stages to identify and construct citation and scientific cooperation networks, to form subject scientific spaces, and, based on them, to devise methods in order to quantify productivity. The results of methods application form the components of the relevant information spaces of scientific activity subjects. The spaces to be built could be used to solve the task of selecting subjects for the implementation of joint scientific and educational projects. In addition, these spaces could be applied to form the organizational and functional framework of the collective scientific activity subjects, including their structural units, which would contribute to ensuring their stable development. Creating the information spaces of scientific activity subjects underlies resolving those issues that would stimulate investment in research and innovation, strengthen cooperation between universities, improve the efficiency and productivity of the scientific enterprise. It has been confirmed experimentally that the potential of a collective subject of scientific activity, including individual subjects, the rate of change of identifiers of whom is positive, would have a non-negative potential. A rate of change in the normalized indicators of identifiers of individual and collective scientific activity subjects has been calculated for the period from January 2019 to December 2020 for three higher education establishments